Knowledge and Attitude of Staff Nurses Towards the Implementation of Play Therapy on Children - Binti Awang, Salmiah; Dioso, Regidor III; Said , Faridah Mohd (The Malaysian Journal of Nursing (MJN), 2022)
Play promotes healing and helps the child to cope with stressful experiences. The study aimed to assess the knowledge and attitude on the implementation of play therapy for children delivered by staff nurses in the Training Institute of the Ministry of Health Malaysia at Kubang Kerian, Kota Bharu, Kelantan. Collected data retrieved from Google survey form from the 95 respondents. There is a relationship between knowledge and attitude (sig<0.05) in the implementation of play therapy for children delivered by staff nurses. Therefore it is concluded that the staff nurses should implement play therapy with the correct knowledge and proper attitude among children confined in the hospital settings.